Juridical Review of the Dissemination of Pornographic Videos Through Social Media - Hudhoifatun Noviva; Bastianto Nugroho; Supolo Setyo Wibowo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
Cases of dissemination of pornographic videos in Indonesia are currently mushrooming and are even in the stage of destroying morals and decency. Social media including electronic media is used by the public to seek information and entertainment. In its development, technology plays an important role, but people often abuse the use of social media, for example being able to access any video including pornographic videos. This type of research uses a qualitative juridical type research method, namely by using a problem approach through a statute approach. The sources and collection of data used in this study are normative. The analysis used in this research is using descriptive analysis method. The purpose of this study was to determine the negative impact of spreading pornographic videos through social media and the efforts made to tackle the spread of pornographic videos through social media according to Law Number 44 of 2008 concerning Pornography. The results of this study explain that the negative impacts of spreading pornographic videos through social media and efforts that can be made in tackling the spread of pornographic videos can be done with preventive and repressive efforts. Another effort is to pass Law Number 44 of 2008 concerning Pornography. As for suggestions given by researchers regarding a juridical review of the dissemination of pornographic videos through social media according to Law Number 44 of 2008 concerning pornography, it is necessary to instill legal awareness within the community that the dissemination pornographic videos are prohibited and violators can be subject to criminal sanctions and there must be firm action from the government and law enforcement agencies in tackling the spread of pornographic videos.